Self-Health Examination Pavilion (APKM) for Health Consultation - Johan, Ahmad Wali Satria Bahari; Montolalu , Billy; T. Rasmana , Susijanto; Yusuf Wicaksono , Ardian; Dzulfikar Fauzi , Muhammad (Journal of Advances in Information and Industrial Technology, 2023)
The Self-Health Examination Platform (APKM) aims to help medical personnel reduce the usual initial examination procedures so that further examinations or consultations can be carried out immediately. The usual initial examinations that are carried out include measuring body weight, height, body temperature, blood pressure, oxygen levels in the blood, number of heart beats per minute, respiratory rate per minute, and an electrocardiogram to record heart activity. All measurements are carried out in one bridge and are equipped with an audio-visual guide. Measurement devices use equipment with a high level of precision and work automatically so that they can be used by ordinary people. However, the results of this examination need to be consulted with a doctor. In this research, it is proposed to develop APKM for telemedicine so that patients who have carried out independent examinations can consult directly with a doctor regarding the results of their examination.